Effects of Spartina alterniflora Invasion on Soil Organic Carbon Storage in the Beihai Coastal Wetlands of China - Huang, Xing; Duan, Yitao; Tao, Yuhua; Wang, Xueping; Long, Haili; Luo, Changsheng; Lai, Yufei (Frontiers in Marine Science, 2022)
The invasion of Spartina alterniflora (S. alterniflora) has changed the carbon cycle process of local ecosystems. In order to clarify the effect of S. alterniflora invasion on coastal soil carbon pool in Northern Beibu Gulf, the distribution characteristics and influencing factors of soil organic carbon (SOC) and SOC storage (SOCS) at different intrusion stages were investigated and analyzed. The results showed that the SOC content in S. alterniflora wetlands (2.65–21.54 g/kg) was higher than that in mudflats (0.85–1.19 g/kg). SOC content in 0–20 cm depth was highest than that in 20–40 cm and 40–60 cm depth. The total SOCS increased by 72.11%, 78.45%, 77.56%, 80.42%, and 90.63% in 3a, 12a, 15a, 16–19a, and 26a compared with mudflats, respectively. S. alterniflora invasion increased SOC and SOCS both in surface soil and deep soil. SOCS increased rapidly during the initial stage of invasion, and remained in a relatively stable and continuous growth state after 12–15 years. The distributions and accumulation of SOC and SOCS were affected mainly by soil texture, soil bulk density, moisture content, total nitrogen and total phosphorus. The source of SOC from S. alterniflora was increasing with invasion ages and would be mainly input in 26a, while marine sources was mainly imported in other invasion ages. Our data indicated that S. alterniflora continuously enhances the SOC sequestration over the years in coastal wetland ecosystems.